Stress Induced Effects for Advanced Polarization Control in Silicon Photonics Components. (22nd June 2008) - Xu, D.-X.; Ye, W. N.; Janz, S.; Delâge, A.; Cheben, P.; Lamontagne, B.; Post, E.; Waldron, P.
Abstract : We review the use of the oxide cladding stress-induced photoelastic effect to modify the polarization dependent properties in silicon-on-insulator (SOI) waveguide components, and highlight characteristics particular to this high index contrast (HIC) systems. The birefringence in SOI waveguides has its origin in the electromagnetic boundary conditions at the waveguide boundaries, and can be further modified by the presence of stress in the waveguiding materials. With typical stress levels inSiO 2 films, which are often used as the upper cladding, the waveguide effective index can be altered anisotropically up to the order of10 − 3 for ridges with heights ranging from 1 μ m to 5 μ m. This effect can be used effectively to counter the waveguide geometrical birefringence, allowing the waveguide cross-section profiles to be optimized for design criteria other than null geometrical birefringence. Design strategies are developed for using stress engineering to achieve a variety of functions. Polarization insensitive arrayed waveguide gratings (AWGs), polarization insensitive ring resonators, and polarization splitters and filters are demonstrated using these design principles.